The Expression of miR-34a in Gingival Crevicular Fluid of Chronic Periodontitis and Its Connection with the TLR/NF-κB Signaling Pathway - Pan, Jiaxin; Liu, Jue; Zhao, Lu (Applied bionics and biomechanics, 2022)
Objective. This study analyzed the expression of miR-34a in gingival crevicular fluid (GCF) of patients with chronic periodontitis and its connection with the Toll-like receptor (TLR)/nuclear factor kappa-B (NF-κB) signaling pathway. Methods. We collected the GCF of the two groups of subjects, using RT-PCR to detect the expression of miR-34a and NF-κB p65 mRNA and TLR4 mRNA and ELISA to detect the inflammatory factor degree in GCF, and performed periodontal examinations on both groups. Results. The gingival index, bleeding index, probe depth, and attachment loss indexes of periodontal examination in the observation group were remarkably superior to those in the control group (P<0.05). The levels of IL-1β, IL-6, and TNF-α in the GCF of the observation group were higher than those of the control group (P<0.05). The mRNA relative expression levels of miR-34a, NF-κB p65, and TLR4 in the GCF of the observation group were dramatically higher than those of the control group (P<0.05). Correlation analysis showed that miR-34a was highly expressed in patients with chronic periodontitis. Conclusion. There is an abnormally high expression of miR-34a in GCF of chronic periodontitis. Its expression is associated with the degree of periodontal inflammation, periodontal tissue damage, and the activation of the TLR/NF-κB signaling pathway and could be used as a potential index for auxiliary diagnosis and severity of the disease.